Is Midtrimester Cervical Length Associated with Preterm Birth in Women Evaluated for Preterm Labor? - O’Connell, Jessica S. (Am J Perinatol, 2017)
OBJECTIVE: This article aims to evaluate whether midtrimester cervical length (CL) is associated with improved prediction of preterm delivery in women presenting with preterm labor. STUDY DESIGN: This is a retrospective cohort study of women with a singleton gestation who underwent routine CL screening between 18 and 24 weeks of gestation between 2010 and 2014 who were later evaluated for preterm labor. Women were stratified by midtrimester CL quartile. Bivariable and multivariable analyses were performed to identify factors independently associated with preterm birth <37 weeks, <34 weeks, and delivery within 7 days of evaluation. Receiver operating characteristic (ROC) curves were created for multivariable equations with and without CL quartile to determine whether addition of CL improved the predictive capacity of the model for predicting preterm birth. RESULT: A total of 460 women were evaluated for preterm labor and had midtrimester CL measurements available. When CL quartile was incorporated into a regression model including demographic and clinical characteristics associated with preterm birth, the area under the ROC curve was not improved (0.775 vs. 0.786, p ¼ 0.20). CONCLUSION: While a shorter midtrimester CL quartile is associated with an increased incidence of preterm delivery in women evaluated for preterm labor, the addition of this variable to an existing model does not improve prediction of preterm birth.